Dampak Perilaku Orang Tua terhadap Kasus Persistensi Gigi pada Anak SD Inpres Unggulan BTN Pemda - Asriawal; Jumriani; Rachman, Latifa Mutmainna; Pariati (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Background: Persistence is the most common dental disease faced by Indonesian people, especially children aged 6-12 years. Because at that age there is a transition period from baby teeth to permanent teeth which is often called the critical period. Seeing the high rates of dental and oral disease, one of which is influenced by parental behavioral factors which play a role in the growth of children's teeth, especially during the mixed dentition period which has an impact on the occurrence of persistence cases. This study aims to determine the effect of parental behavior on tooth persistence in students of SD Inpres Unggulan BTN Pemda. Method : The research method used is cross sectional. This type of research is descriptive quantitative. The sample in this study were 36 parents of students whose children had persistent teeth which were taken using a purposive sampling technique based on inclusion and exclusion criteria. This research was conducted at the Pemda BTN Superior Inpres Elementary School in January-March 2023. Results: Data analysis was carried out using a bivariate test with the chi square and kruskal wallis methods. Based on the Chi Square test obtained p 0.001 with a correlation coefficient of 0.05. Based on the results of the Kruskal Wallis test, the category mean rank was 35.00 with a p-value of 0.001 (p <0.05). The results of statistical tests in this study found that parental behavior based on aspects of knowledge, attitudes and actions had an impact on persistent tooth cases. Conclusion: Lack of knowledge has an impact on parental ignorance as a trigger for persistence. Attitude has less impact on parents who are unable to respond to cases of persistent teeth. Good behavior impacts a parent's ability to prevent and treat persistent teeth.  Keywords : Parental behavior, tooth persistence